2021
DOI: 10.1186/s12889-021-11278-7
|View full text |Cite
|
Sign up to set email alerts
|

Using intervention mapping to develop ‘Healthy HR’ aimed at improving sustainable employability of low-educated employees

Abstract: Background The perspectives of low-educated employees are often neglected when designing sustainable employability (SE) interventions. As a result, the interventions offered by the employer do often not align with the needs of low-educated employees. This particular group should therefore be actively involved in the process of developing and implementing SE interventions in their work organizations. The current paper describes the development process of a web-based intervention for HR managers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The challenge for supervisors is to set clear expectations and give concrete instructions about work tasks. This is in line with previous research showing that good and open communication between the supervisor and the employee is important to discuss adjustments of work tasks or in the work environment [21,25], as this may increase job satisfaction and thereby sustainable employability of employees with a work disability [27].…”
Section: Working Conditions and Working Relationssupporting
confidence: 89%
“…The challenge for supervisors is to set clear expectations and give concrete instructions about work tasks. This is in line with previous research showing that good and open communication between the supervisor and the employee is important to discuss adjustments of work tasks or in the work environment [21,25], as this may increase job satisfaction and thereby sustainable employability of employees with a work disability [27].…”
Section: Working Conditions and Working Relationssupporting
confidence: 89%
“…A systematic review has demonstrated that significant increases were observed in the uptake of disease prevention interventions [ 33 ]. In addition, IM has been used in a wide range of health promotion programs, targeting different populations (e.g., employees, older adults), in different contexts (e.g., workplaces, schools), and using different delivery modes (e.g., mHealth, web-based) [ 14 , 34 , 35 , 36 , 37 , 38 ]. Therefore, the IM approach is a promising tool to develop an intervention to improve PA and health in working adults, which may boost the effectiveness of the intervention and increase reliability of conclusions in this area.…”
Section: Resultsmentioning
confidence: 99%
“…This implication is supported by the recent promising scientific literature that overall underlines the importance of enabling valuable work practices for SE. These practices mainly take shapes in a dialogue-based toolkit [62,63]; health and safety monitoring routines [64]; tailormade development programs [65]; the promotion of opportunities and employee development fitted with personal wishes and needs [66]; negotiation and discussion about Ideals and systematic training as well as structured conversation processes and coaches [67]; the improvement of the employee psychological capital [68]; job crafting and continuous sustainable changes [69]; continuous routines of conditions' assessments and shared action plans [70]; career development discussions as well as regular dialogue and organizational culture [71]; and counseling, coaching, mentoring and motivational interviewing [60]. Therefore, developing capabilities in the form of competencies and health resources should be considered a key action in SE promotion and requires further practical advancement.…”
Section: Practical and Societal Implicationsmentioning
confidence: 99%